Persepsi Pengguna Terhadap Penataan Wisata Lahor, di Perbatasan Kabupaten Malang dan Kabupaten Blitar - Relyndo, Singla; Ir. Jenny Ernawati, MSP, Ph.D, CIQnR, CIQaR (Jurnal Mahasiswa Departemen Arsitektur, 2024)
Abstract: According to Regional Regulation No.3 of 2010 concerning Malang Regency Regional Spatial Planning, Lahor Tourism is one of the favorites. The number of tourists coming to Lahor Tourism experienced a drastic decline in 2020 due to the Covid-19 pandemic. During the new normal period, the number of visitors to Lahor Tourism has gradually increased, but this increase in visitors has not been as strong as before the Covid-19 pandemic occurred. A good tourist area can be reflected in a well-organized spatial arrangement to create attraction. In realizing good planning, of course it is necessary to pay attention to tourism aspects to support tourism activities so that tourism continues to develop. The research aims to determine user perceptions (visitors and the public) regarding Lahor Tourism arrangements. The method used in this research is a quantitative method with a descriptive approach. Quantitative data processing was carried out using questionnaires which were then analyzed using grouping of average values analysis. The variables used in the research include attractions, accessibility, amenities, additions, security and cleanliness. Research obtained shows that Lahor Tourism has good attraction and additional factors, while accessibility, amenities, and security and cleanliness are not good. Keywords: perception, arrangement, attraction, tourism aspects